THE USE OF SPINNING WHEEL AS A MEDIA IN LEARNING SPEAKING ABILITY - Muhammad Khoerul Hadist; Ana Ratnasari; Hidjanah; Vera Claudi Ristiani (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2022)
This research is a qualitative research. The purpose of this study was to find out how to use the spinning wheel as a media in learning speaking ability. The writer conducted this research in terms of the use of the Spinning Wheel as a media in learningspeaking ability. The writer used questionnaires and interviews for data collection. The results showed that students felt more confident in their ability to speak English with positive results in all participants. The students also have fun learning to used these media. The students feel that learning to speak greatly increases their self-confidence. Spinning Wheel media is very helpful in understanding a material when students learn so that students do not feel bored while studying.